Progressive Ataxia and Neurologic Regression in RFXANK-Associated Bare Lymphocyte Syndrome. (June 2021) - Alharby, Essa; Obaid, Mona; Elamin, Mohammed A.O.; Almuntashri, Makki; Bakhsh, Ismail; Samman, Manar; Peake, Roy W.A.; Alasmari, Ali; Almontashiri, Naif A.M.
Abstract : Objective: To identify the genetic cause of a late-onset immunodeficiency and subacute progressive neurodegenerative disease affecting cognition, motor, visual, and cerebellar systems in a patient with a family history of 2 younger siblings with an early-onset immunodeficiency disease. Methods: Physical examinations, immunologic, brain MRI, whole-exome sequencing, and segregation studies were used to identify the genetic and neuroimmunologic etiology of disease in this family. Results: We identified a homozygous loss-of-function (LOF) mutation (c.271+1G>C) in the RFXANK gene in the index patient and one of his younger affected siblings. Biallelic mutations in the RFXANK gene are known to cause bare lymphocyte syndrome (BLS) type II, complementation group B. The clinical and immunologic investigations were consistent with a clinical diagnosis of BLS type II. MRI demonstrated global cerebral and cerebellar atrophy with white matter signal changes in the index case. Conclusions: In addition to BLS type II, our study has expanded and further characterized the phenotype associated with the LOF of RFXANK to include progressive neurodegenerative disease. Our study also provides evidence for the impact of LOF on brain development and function. Thus, early bone marrow transplantation, as a standard of care for BLS, could prove to be protective against the neurologic phenotypes in this group of patients.